1997
DOI: 10.1627/jpi1958.40.500
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodenitrogenation of Carbazole on Nitrided Molybdena-alumina Catalyst.

Abstract: The hydrodenitrogenation (HDN) of carbazole on the nitrided 12.5% MoO3/Al2O3 catalysts over a temperature range of 280-360℃ and at a total pressure range of 5-15MPa was studied. The 12.5% MoO3/Al2O3 was nitrided at various nitriding temperatures (500, 700 and 900℃), NH3 pressures (0.1 and 0.5MPa), and NH3 flow rates (4 and 15l h-1), following after the temperature-programmed reaction with NH3. After nitriding, the nitrided catalysts were cooled to room temperature in flowing NH3 and passivated with 1% O2/He fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…In this study, we explore the capabilities of cyclic IMS high-resolution mass spectrometry for the description of petrochemical sample materials with high isobaric and isomeric complexity. For this purpose, fossil vacuum gas oils (VGOs), a heavy residue of petroleum refining, were chosen. ,, Different types of experimental designs are presented. This manuscript is organized along the questions resulting from the isobaric and isomeric continuum: How far can we increase the isomeric separation capability for the direct infusion of petroleum?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we explore the capabilities of cyclic IMS high-resolution mass spectrometry for the description of petrochemical sample materials with high isobaric and isomeric complexity. For this purpose, fossil vacuum gas oils (VGOs), a heavy residue of petroleum refining, were chosen. ,, Different types of experimental designs are presented. This manuscript is organized along the questions resulting from the isobaric and isomeric continuum: How far can we increase the isomeric separation capability for the direct infusion of petroleum?…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, fossil vacuum gas oils (VGOs), a heavy residue of petroleum refining, were chosen. 11,42,43 Different types of experimental designs are presented. This manuscript is organized along the questions resulting from the isobaric and isomeric continuum: How far can we increase the isomeric separation capability for the direct infusion of petroleum?…”
Section: ■ Introductionmentioning
confidence: 99%
“…As a new emphasis, the research on the HDN and its competition with HDS is lacking, especially for carbazoles 13‐15 . While the reaction network for the HDN of carbazoles has long been established by Nagai et al 16 in 1980, by now a corresponding kinetic model has not been reported, which is not commensurate with the predominance of carbazoles in refractory diesel. Similarly, though the organonitrogen inhibition has been well‐studied, most of them were conducted in steady‐state and with little removal of organonitrogen species 17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…The HDN reaction on molybdenum sulfides has been extensively studied in terms of further development of NiMo and CoMo sulfides with additives containing phosphorus and fluorine, competitive reaction with HDS and the effect of the generated H 2 S, and the active surface sites [1][2][3][4][5][6][7][8][9][10]. In recent years, new types of catalyst, such as transition metal nitrides and oxynitrides [11][12][13][14] have been studied for hydrotreatment [15][16][17], HDS [18][19][20][21][22][23] and HDN [24][25][26][27][28][29][30][31][32][33][34]. Molybdenum nitrides with a high surface area have been extensively developed by the temperature-programmed nitridation of MoO 3 with ammonia [35][36][37][38][39] or N 2 ?…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, phosphorus-doped tungsten oxynitride has been prepared from heteropolyanion precursors [48]. Attention has been directed to a number of different areas, including (1) the preparation of bimetallic nitride catalysts, such as Co, Ce, Ti, and Zr-doped Mo nitrides with higher HDN activities than the pure c-Mo 2 N catalyst [42,[49][50][51][52]; (2) the specific reactivity of nitrogen compounds, such as indole [26,31], pyridine [30,[32][33][34], quinoline [24] and carbazole [25,28,29], on Mo 2 N and promoted Mo 2 N/Al 2 O 3 catalysts for C-N hydrogenolysis; (3) the activities of bulk molybdenum nitride and nitrided Mo/Al 2 O 3 in comparison to sulfided catalysts for HDN [28,53] (in the latter case, nitrides are more active), although molybdenum sulfide and sulfided NiMo/c-Al 2 O 3 catalysts were more active than the corresponding nitride for the HDN and HDS of coal-derived naphtha [17] and the light gas and heavy gas oils [54], respectively, at higher temperatures ([598 K)); (4) the kinetics of the Mo 2 N/Al 2 O 3 catalyst for HDN [22,55,56] including the competitive reaction with HDS and the effects of additives and catalyst deactivation [22,54,57]; and (5) the active surface sites on Mo 2 N/Al 2 O 3 catalysts which have been studied using XPS [55,[58][59][60], NMR [61,62], the temperature-programmed desorption(TPD)/temperature-programmed surface reaction with hydrogen (TPSR) [58,[63][64][65]…”
Section: Introductionmentioning
confidence: 99%